A Modified Semisolid Clonal Culture for Identification of B-1 and B-2 Progenitor Colony Forming Ability of Mouse Embryonic Hemogenic Endothelial Cells - Kobayashi, Michihiro (Bio Protoc, 2020)
The search for the origin of the first hematopoietic stem cells (HSCs) in the mouse embryo has been a hot topic in the field of developmental hematopoiesis. Detecting lymphoid potential is one of the supportive evidence to show the definitive hematopoietic activity of HSCs. However, the first B-lymphoid potential in the mouse embryos are reported to be biased to innate-like B-1 cell lineage that can develop from hemogenic endothelial cells (HECs) independently of HSCs. On the other hand, conventional adaptive immune B cells (B-2) cells are considered to be exclusively derived from HSCs. Therefore, segregating B-1 and B-2 progenitor potential is important to understand the developmental process of HSCs that are also produced from HECs through intermediate precursors referred to as pre-HSCs. Both HECs and pre-HSCs show endothelial surface phenotype and require stromal support to detect their hematopoietic activity. The method utilizing stromal cell culture followed by modified semisolid clonal culture enables us to detect the number of colony forming units for B-1/B-2 progenitors originally derived from HECs/pre-HSCs, which will reflect the potential of B-1 biased or multi-lineage repopulating HSCs.